Faktor Promosi dan Sarana Prasarana Dalam Meningkatkan Kunjungan Wisatawan Di Objek Wisata Danau Tasikardi Serang - Banten - Widiachandra Wahyudi; Mochamad Herlan (JURNAL DESTINASI PARIWISATA, 2021)
The purpose of this study describes the promotion and facilities factors that improve tourist visits in Tasikardi tourism object, Serang - Banten. The used research method was qualitative research. The used data analysis was descriptive qualitative data analysis. The data analysis technique used data analysis techniques based on Miles & Huberman (1994): data collection, data reduction, data display, and conclusions. The results of this study were the promotion factors are still not optimal to increase tourist visits on the tourism object of Tasikardi. This happens because there are still many tourists who do not fully get information through promotion media and not yet optimal to utilize promotion media. Facilities factors are still not maximal to increase tourist visits on the tourist object of Tasikardi. The results are due to the amenities, access, and completeness of the available facilities in the tourism object of Tasikardi, which have still not given a good perception of visitors or its governments. Keyword: Promotion; Facilities; Tasikardi